Genome-wide identification, evolutionary expansion and expression divergence of the AP2/ERF gene family in loquat (Eriobotrya japonica) - Yumeng Liu; Linqi Cai; Xiurun Fan; Huiling Zhang; Minghui Chen; Yue Lin; Junwei Chen; Kai Xu; Boping Wu (Fruit Research)
Loquat (Eriobotrya japonica) is a subtropical evergreen fruit tree with high economic benefits and nutritional value. AP2/ERF (APETALA2/ethylene responsive factor) are a wide range of transcription factors found in plants, which play an important role in regulating plant development and biological processes. However, the systematic identification and characterization of AP2/ERF genes in loquat remains unclear. In the present research, a total of 189 loquat AP2/ERF members were identified. According to the phylogenetic tree, these members were divided into three subfamilies, including AP2 (42), ERF (96), and DREB (51). Except for three genes located on the skeleton, most of the loquat AP2/ERF genes were unevenly distributed across all chromosomes. The collinearity results showed that 175 duplicate gene pairs were found in the AP2/ERF gene family of loquat. Ka/Ks results indicated that these genes underwent purification selection pressure. The syntenic analysis of AP2/ERF genes between Arabidopsis, pomegranate, peach, and loquat provided valuable clues for the potential evolution of AP2/ERF family in loquat. Cis-element analysis showed that most of the AP2/ERF genes in loquat had multiple cis-elements related to stress response, plant hormone signal transduction, and plant growth and development. Transcriptomic data indicated that the expression patterns of AP2/ERF genes exhibited diversity in different loquat cultivars during fruit development and ripening. The results of this study displayed the first comprehensive analysis of AP2/ERF genes in loquat, which provides a solid foundation for future research on the function of AP2/ERF genes in loquat.